The aesthetics of visual construction in Iranian TV drama: (Al-Mukhtar Al-Thaqafi series) as a model - Musa, Salwan Baha Kadhim (Al-Adab Journal, 2022)
The research is summarized as it addresses the issue of the aesthetics of the visual structure in the Iranian drama, which the filmmaker's resort to in order to build an image that understands the philosophical and aesthetic variables in order to convey meanings, connotations and metaphors of its concept to the recipient, as the image itself is imaginary and at the same time it seeks to change in order to build its image. The external through the use of the elements of the visual structure through the movement of the camera, the aesthetic use of lighting, the embodiment of color, the expressiveness of the montage, and the use of visual effects. The film structure and its elements and increases the attraction of the recipient to interact with the context of the dramatic work.